AKTIVITAS ANTIOKSIDAN EKSTRAK HIPOKOTIL Bruguiera gymnorhiza PADA PELARUT DAN FASE KEMATANGAN YANG BERBEDA - Sri Handayani (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
The research objective was to determine the best treatment from the results of the antioxidant test, phenol content, tannins and the yield of crude extract of hypocotyl B. gymnorhyza in the mature phase in solvents with different levels of polarity. The sample extraction was carried out using a single maceration method with organic solvents according to the experimental treatment. Soaking the simplicia powder in a suitable solvent (1: 5) for 3 x 24 hours in a dark and closed container. During maceration, the samples were placed in a dark room and solvent replacement is is carried out every 24 hours. The filtrate is then evaporated vacuum at a temperature according to the boiling point of each solvent. Each treatment extract was then tested for its antioxidant strength (IC50), total phenol, tannin content and yield. The results showed that the best treatment was purple hypocotyl aceton extract of B. gymnorhiza, with an antioxidant power (IC50) of 3.98 ppm, total phenol 21.61 mg.GAE/100 mg extract, tannin 59.20 ppm and yield 4.10%bk simplicia.